2013
DOI: 10.1007/s00428-013-1470-9
|View full text |Cite
|
Sign up to set email alerts
|

BRAF mutation in sporadic colorectal cancer and Lynch syndrome

Abstract: The aim of the study was to detect mutations of BRAF oncogene in colorectal cancer and to use this information to identify Lynch syndrome patients. Consecutive cases of primary colorectal cancer (n = 137) were analyzed for MLH1 protein expression using immunohistochemistry (IHC). BRAF V600E mutation was detected by IHC using a specific monoclonal antibody (VE1) and by qPCR. All MLH1 protein-negative cases were subjected to microsatellite instability analysis and MLH1 promoter methylation assay. MLH1 protein ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
76
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 34 publications
7
76
0
3
Order By: Relevance
“…In 11 studies BRAFV600E mutation specific IHC has either outperformed or performed comparably to molecular techniques [2], [7], [8], [9], [10], [11], [12], [13], [14],[15],[16] whereas in two studies mutation specific IHC was found to be less reliable. [17], [18] A fair reading of the literature would support the approach taken by Kuan et al, [12] that mutation specific IHC is reliable but requires rigorous technical optimization and ongoing quality assurance including the performance of molecular testing in equivocal cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 11 studies BRAFV600E mutation specific IHC has either outperformed or performed comparably to molecular techniques [2], [7], [8], [9], [10], [11], [12], [13], [14],[15],[16] whereas in two studies mutation specific IHC was found to be less reliable. [17], [18] A fair reading of the literature would support the approach taken by Kuan et al, [12] that mutation specific IHC is reliable but requires rigorous technical optimization and ongoing quality assurance including the performance of molecular testing in equivocal cases.…”
Section: Discussionmentioning
confidence: 99%
“…In the interim, the combination of BRAFV600E and MMR IHC still has a clear role in the triaging of patients with CRC encountered in routine clinical practice for formal molecular testing for Lynch Syndrome. [2], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16] The strong likelihood that this approach can also have the added benefit of predicting outcome can be considered a likely downstream benefit of universal screening for Lynch Syndrome by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Sporadic MSI CRC are associated with BRAF V600E mutations [28] and occur preferably in older patients [42]. Since BRAF V600E mutations virtually exclude LS, it as a suitable test to differentiate between sporadic CRC with hMLH1 mutation and LS [43]. In this study, all patients with MMR-D who fulfilled AC, BG and rBG had no mutation in BRAF V600E.…”
Section: Discussionmentioning
confidence: 99%
“…2, 8, 9, 10 To date, its main suggested utility has been to triage molecular testing for Lynch syndrome in mismatch repair-deficient tumors. It has been proposed that if BRAFV600E immunohistochemistry were performed universally in all tumors, it could also be used to detect the poor prognosis mismatch repair-proficient BRAFV600E mutant colorectal carcinomas.…”
mentioning
confidence: 99%